2001
DOI: 10.1016/s0960-9822(01)00096-3
|View full text |Cite
|
Sign up to set email alerts
|

A role for Drosophila SMC4 in the resolution of sister chromatids in mitosis

Abstract: Our results demonstrate that SMC4 is critically important for the resolution of sister chromatids during mitosis prior to anaphase onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
201
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(231 citation statements)
references
References 41 publications
29
201
1
Order By: Relevance
“…It can be speculated that impaired association of condensation factors on hyperacetylated chromatin may alter the dissociation of cohesins during early mitotic stages, resulting in persistent cohesion along chromatid arms. The separin-dependent release of centromeric cohesins at anaphase onset would promote the formation of chromatin bridges between sister chromatids due to poor sister chromatid arm resolution, as already reported for condensin mutants (Bhat et al, 1996;Ouspenski et al, 2000, Steffensen et al, 2001 or after inhibition of sister chromatid decatenation by topoisomerase II inhibitors (Cimini et al, 1997). On the other hand, a lack of sister chromatid separation at the centromere level is clearly indicated by the observation of chromatin bridges spanning the centromeric region.…”
Section: Histone Hyperacetylation Prevents Sister Chromatid Resolutiosupporting
confidence: 65%
“…It can be speculated that impaired association of condensation factors on hyperacetylated chromatin may alter the dissociation of cohesins during early mitotic stages, resulting in persistent cohesion along chromatid arms. The separin-dependent release of centromeric cohesins at anaphase onset would promote the formation of chromatin bridges between sister chromatids due to poor sister chromatid arm resolution, as already reported for condensin mutants (Bhat et al, 1996;Ouspenski et al, 2000, Steffensen et al, 2001 or after inhibition of sister chromatid decatenation by topoisomerase II inhibitors (Cimini et al, 1997). On the other hand, a lack of sister chromatid separation at the centromere level is clearly indicated by the observation of chromatin bridges spanning the centromeric region.…”
Section: Histone Hyperacetylation Prevents Sister Chromatid Resolutiosupporting
confidence: 65%
“…Inhibition of condensin blocks the ability of mitotic Xenopus extracts to reorganize sperm chromatin into linear rod-shaped chromosomes (5,6), suggesting an essential role in chromosome compaction and resolution. However, inhibiting condensin in Drosophila (7,8), Caenorhabditis elegans (9), and vertebrate cells (10,11) delays, but does not prevent, compaction. The compacted chromosomes that form after condensin inhibition are sensitive to hypotonic fixation conditions and exhibit defects during alignment and segregation that suggest compromised structural integrity (1).…”
mentioning
confidence: 99%
“…2B). 13 We found that, even in overcondensed wt metaphase chromosomes, sister chromatids appeared resolved in most cells (79%) However, sister chromatids were only resolved in 46% of prometaphase/metaphase mutant neuroblasts (Fig. 2B).…”
mentioning
confidence: 80%
“…The chromosome missegregation phenotype of Polo-depleted cells resemble the ones described for lack of SMC4 (structural maintenance chromosome 4) and Topoisomerase II, proteins required for chromosome resolution. [11][12][13] Interestingly, Plk1-dependent phosphorylation of Topoisomerase II is essential for its function in chromosome segregation during mitosis. 14 We therefore examined prometaphase/ metaphase chromosome resolution in Polo-depleted cells.…”
mentioning
confidence: 99%